Mekanisme Adaptasi Korban PHK Akibar Covid-19 - Rumagit, Tannia Christina (FOCUS, 2024)
The Covid-19 virus pandemi has significantly impacted the global economy. This crisis has disrupted Indonesia's economy as well, with one of the implications being a 4% decrease in economic growth, potentially even lower depending on the duration and severity of the pandemi. This situation has forced many companies to lay off employees, leaving the victims of these layoffs to adapt and find ways to survive during the pandemi. This research utilizes resilience theory and employs observation and interview methods. The observation technique involves narrative observation, where the observer records the behavior of the subjects. The research also utilizes the Moderately Scheduled Interview method and the Topical Sequence Technique. Based on the observations conducted, neither of the subjects has demonstrated resilience. However, the interviews revealed that the subjects engaged in many new activities during the pandemi, which could enhance their resilience.